CAN WOM (WORD OF MOUTH) BEAT E-WOM (ELECTRONIC-WORD OF MOUTH) ON THE DECISION TO VISIT AMPERA 2 TAK RESTAURANT, BINTARO BRANCH? - Nurbaeti Nurbaeti; Himawan Brahmantyo (LPPM STIE Muhammadiah Bandung, 2022)
This study aims to determine how much influence WOM and E-WOM have on the decision to visit Ampera 2 Tak Restaurant Bintaro Branch. This type of research is descriptive with a quantitative approach and multiple regression analysis methods. Data collection techniques by distributing questionnaires. The population in this study were all consumers who visited the Ampera 2 Tak Veteran Bintaro Restaurant. At the same time, the sample in this study amounted to 100 respondents. The sampling technique uses accidental sampling. The results show that E-WOM is far superior in influencing product sales than WOM because of the greater reach of E-WOM than WOM which connects many people without geographical boundaries so that it has power, also has many opportunities to exchange information via any internet site and social media for free. Suggestions for the Ampera 2 Tak Veteran Bintaro Restaurant to improve product and service quality so that consumers feel satisfied and make positive comments on social media.